Pre-entry Attributes and Academic Persistence at the Master’s Level in Science and Technology in Burkina Faso: The Mediating Role of University Experience - Loye, Alexis; Frenette, Eric; Kobiané, Jean-François (Mesure et évaluation en éducation, 2020)
The purpose of this research is to analyze the effect of the university experience (scholarship, repetition) on the relationship between pre-entry attributes (father’s occupation, gender, place of birth, age at first enrollment, field of study in high school, graduate point average [GPA], university enrollment delay in the university, university reform) and academic persistence in master’s degree in science, technology, engineering, and mathematics (STEM) at a university in Burkina Faso. Cox regression and modern mediation analyses are used on longitudinal data from 14 cohorts of freshmen (n = 13,891). Findings revealed indirect-only mediation (father’s occupation [other], field of study in high school, age at first enrollment), complementary mediation (GPA), competitive mediation (university enrollment delay, university reform), and an absence of mediation (direct-only) for gender. There is no mediating effect for the place of birth and the father’s salaried profession. Scholarship programs as well as appropriate reforms and policies aiming to reduce repetition are required to improve academic persistence in master’s degree in STEM.